Thermal simulation of green roof in container buildings - Gonçalves, Fernanda Barros (2024)
The increasing number of environmental issues has been encouraging the use of green technologies in civil construction. Over time, technologies emerge and their use is encouraged by the government, by the benefits they bring to users and also by the economy it generated. One of these technologies is the green roof, which helps to increase the permeable area of the city, and in terms of thermal and acoustic comfort. Another solution is the use of containers to replace masonry in civil construction, which reduces expenditures and construction timing. Previously both solutions were studied experimentally in reduced-scale modules in order to analyze the influence of the substrate thickness on the heat flow. In order to evaluate the influence of the substrate thickness in an environment closer to a real construction, simulations were carried out using the EnergyPlus program to evaluate the internal temperature of an environment with a green roof in its construction and with natural ventilation